MENTAL HEALTH PROBLEM DURING COVID-19 PANDEMI - Muhammad Rachmadi - (Yayasan Pendidikan Medika Indonesia, 2021)
The COVID-19 pandemic has had many impacts on mental health. Many studies have found that there is a relationship between the incidence of the long-standing Covid-19 pandemic and an increase in the incidence of mental health disorders. Some of the mental disorders that are then caused include: post-traumatic stress disorder (PTSD / Post-Traumatic Stress Disorder), secondary traumatic stress (STS), burnout, anxiety and obsessive compulsive disorder. A large-scale survey study has been carried out by several researchers to further assess the impact of this Covid-19 incident, especially on mental health. This paper will summarize the latest research on some of these diseases in the literature in recent years